Children should learn to appreciate Science, Mathematics and Technology in School. Shouldn't Scientists, Mathematicians and Technologists all help? - Keen, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary The nation does not appreciate science, mathematics and technology, all central to the future of the country and the planet. The Natural Science and Engineering Research Council of Canada worries about the supply of professionals in these fields for the next century. We have too few women in science, technology and mathematics. Education in science, mathematics and technology should start in the schools. The nation has many professionals in industry, the universities and government agencies. A national scientific society could lead and co-ordinate a long-term nation-wide program to bring a significant fraction of these professional scientists, mathematicians and technologists into the schools, enhancing educational programs. The program would complement the efforts of teachers of science, technology, and mathematics, and would have to be integrated with the normal curriculum — emphasizing basic principles. Interaction would have to be intense at the local level, between local science, technology and mathematics groups and institutions on the one hand, and teachers and school boards on the other. Employers would provide the time. Provinces through schoolboards and schools would provide the travel and lodging expenses. Successful analogues are the various provincial and national programs of "Writers-in-the-Schools". Scientists, mathematicians and technologists, better funded to start with, should be able to do at least as well. Scientists, mathematicians and technologists would serve the nation well.